Pengaruh ROA, Terhadap Harga Saham Dengan Price To Book Value Sebagai Variabel Mediasi Perusahaan Indeks LQ45 Di BEI - Cokorda Krisna Yudha; I Gusti Ayu Ratih Permata Dewi; I Gusti Agung Ayu Kartika Dewi (ARTHA SATYA DHARMA, 2022)
This study aims to examine the effect of return on assets on price to book value, price to book value and return on assets on stock prices, examine the role of price to book value in mediating the effect of return on assets on stock prices. This research was conducted at LQ45 companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The sample used was 23 companies which were determined by purposive sampling technique. The data analysis technique used is path analysis which is processed with the help of SPSS 18.0 for Windows software. The results showed that return on assets had a significant positive effect on price to book value; price to book value has a significant positive effect on stock prices; return on assets has a significant positive effect on stock prices. This study also shows that price to book value is able to mediate the effect of return on assets on stock prices.